Spectroscopy and characterization of nanomaterials and novel materials : experiments, modeling, simulations, and applications - Ohio Library and Information Network (Weinheim, Germany : Wiley-VCH, 2022)
This book deliver a practical and up-to-date exploration of the characterization and applications of nanomaterials and other novel materials, including quantum materials and metal clusters. The contributions cover spectroscopic characterization methods for obtaining accurate information on optical, electronic, magnetic, and transport properties of nanomaterials. The book reviews nanomaterial characterization methods with proven relevance to academic and industry research and development teams, and modern methods for the computation of nanomaterials' structure and properties - including machine-learning approaches - are also explored. Readers will also find descriptions of nanomaterial applications in energy research, optoelectronics, and space science, as well as: A thorough introduction to spectroscopy and characterization of graphitic nanomaterials and metal oxides; Comprehensive explorations of simulations of gas separation by adsorption and recent advances in Weyl semimetals and axion insulators; Practical discussions of the chemical functionalization of carbon nanotubes and applications to sensors; and In-depth examinations of micro-Raman imaging of planetary analogs
Front Matter -- Spectroscopy and Characterization. Spectroscopic Characterization of Graphitic Nanomaterials and Metal Oxides for Gas Sensing / Olasunbo Farinre, Hawazin Alghamdi, Prabhakar Misra -- Low-dimensional Carbon Nanomaterials: Synthesis, Properties, and Applications Related to Heat Transfer, Energy Harvesting, and Energy Storage / Mahesh Vaka, Tejaswini Rama Bangalore Ramakrishna, Khalid Mohammad, Rashmi Walvekar -- Mesoscale Spin Glass Dynamics / Samaresh Guchhait -- Raman Spectroscopy Characterization of Mechanical and Structural Properties of Epitaxial Graphene / Amira Ben Gouider Trabelsi, Feodor V Kusmartsev, Anna Kusmartseva, Fatemah Homoud Alkallas -- Raman Spectroscopy Studies of III - V Type II Superlattices / Henan Liu, Yong Zhang -- Dissecting the Molecular Properties of Nanoscale Materials Using Nuclear Magnetic Resonance Spectroscopy / Nipanshu Agarwal, Krishna Mohan Poluri -- Charge Dynamical Properties of Photoresponsive and Novel Semiconductors Using Time-Resolved Millimeter-Wave Apparatus / Biswadev Roy, Branislav Vlahovic, MH Wu, CR Jones -- Metal Nanoclusters / Sayani Mukherjee, Sukhendu Mandal -- Modeling and Simulation. Simulations of Gas Separation by Adsorption / Hawazin Alghamdi, Hind Aljaddani, Sidi Maiga, Silvina Gatica -- Recent Advances in Weyl Semimetal (MnBi 2 Se 4) and Axion Insulator (MnBi 2 Te 4) / Sugata Chowdhury, Kevin F Garrity, Francesca Tavazza -- Applications. Chemical Functionalization of Carbon Nanotubes and Applications to Sensors / Khurshed Ahmad Shah, Muhammad Shunaid Parvaiz -- Graphene for Breakthroughs in Designing Next-Generation Energy Storage Systems / Abhilash Ayyapan Nair, Manoj Muraleedharan Pillai, Sankaran Jayalekshmi -- Progress in Nanostructured Perovskite Photovoltaics / Sreekanth Jayachandra Varma, Ramakrishnan Jayakrishnan -- Applications of Nanomaterials in Nanomedicine / Ayanna N Woodberry, Francis E Mensah -- Application of Carbon Nanomaterials on the Performance of Li-Ion Batteries / Quinton L Williams, Adewale A Adepoju, Sharah Zaab, Mohamed Doumbia, Yahya Alqahtani, Victoria Adebayo -- Space Science. Micro- R aman Imaging of Planetary Analogs: Nanoscale Characterization of Past and Current Processes / Dina M Bower, Ryan Jabukek, Marc D Fries, Andrew Steele -- Machine Learning and Nanomaterials for Space Applications / Eric Lyness, Victoria Da Poian, James Mackinnon
Includes index
Keywords: Nanostructured materials -- Spectra; Nanostructured materials -- Analysis; Electronic books